Memory Impairment and Executive Dysfunction are Associated with Inadequately Controlled Diabetes in Older Adults - Ellen Grober PhD; Charles B. Hall PhD; Steven R. Hahn MD; Richard B. Lipton MD (SAGE Publishing, 2011)
Objective: To assess the cross-sectional relationship of glycemic control to memory impairment and executive dysfunction in older adults with diabetes treated at an urban primary care center. Participants and Methods: As part of a primary care-based cognitive screening program, we identified adults age 65 or older with a diagnosis of diabetes. Glycosylated hemoglobin level (HbA1c) was used to define diabetes as controlled (HbA1c <7) or inadequately controlled(HbA1c ≥ 7). Episodic memory was measured by quartile of free recall scores on the Free and Cued Selective Reminding Test. Executive function was measured using an ordinal composite score derived from animal fluency and months backward. These were the main predictors of diabetic control. Results: The 169 participants with diabetes had a median age of 74. The sample was 38% African American and 42% Latino. One hundred four (61%) had inadequately controlled diabetes. Memory impairment and executive dysfunction were independent predictors of diabetic control after adjusting for age and education. Binary logistic regression models indicated that the odds of inadequately controlled diabetes was higher for patients in the worst quartile of memory functioning compared to patients in higher quartiles of memory functioning (odds ratio = 6.4; 95% confidence interval: 2.3, 17.6). Any level of executive dysfunction increased the odds of inadequately controlled diabetes compared to patients in the best quintile of executive functioning (odds ratio = 3.6; 95% confidence interval: 1.58, 8.35). Conclusions: Memory impairment and executive dysfunction were associated with inadequately controlled diabetes. Though causal inferences are not robust in a cross-sectional study, we suggest that cognitive dysfunction may interfere with diabetes management and that inadequate diabetic control may contribute to cognitive dysfunction.